Monitoring the impact of COVID-19 in Myanmar: Agricultural equipment retailers - June 2020 survey round - Takeshima, Hiroyuki; Win, Myat Thida; Masias, Ian (International Food Policy Research Institute, 2020)
Agricultural equipment retailers (ER) in Myanmar were originally interviewed by telephone in late May 2020 to determine how their businesses were being affected by COVID-19 related restrictions. The results of that survey were published in Myanmar Strategy Support Program Policy Note 09. To trace the continuing impact of the COVID-19 pandemic on their economic activities, a second phone survey of ERs was done in late June 2020. This Policy Note reports on the results of this second survey.